Dramatization: Learning by competences through interartistic dialogue - Mociño González, Isabel; Agrelo-Costas, Eulalia (Pulso. Revista de educación, 2023)
Early childhood education teacher training should foster reading competence and the capacity to connect literary reading with other artistic manifestations. We believe that dramatization is one of the most effective strategies to achieve this, which is a transversal instrument based on interartistic dialogue. This research intends to describe the design, implementation and results of a didactic experience linked to dramatizations, which has been carried out with students from two faculties of educational sciences. The methodology used in this classroom experience was participatory action research and collaborative work was used as a support for the training process. The results show the satisfaction of the participating students, the effectiveness of the strategies used in the teaching practice, the construction of meaningful learning, the improvement of the reading-literary mediation capacity and the promotion of reading habits. It is concluded that dramatization is an effective strategy in the development of multiple competences associated with, among others, expression, constructive collaboration and creative thinking, with comprehensive reading being the motivator of the whole experience.